Cellular Source and Mechanisms of High Transcriptome Complexity in the Mammalian Testis - Magali Soumillon; Anamaria Necsulea; Manuela Weier; David Brawand; Xiaolan Zhang; Hongcang Gu; Pauline Barthès; Maria Kokkinaki; Serge Nef; Andreas Gnirke; Martin Dym; Bernard de Massy; et al. (Cell Reports, 2013)
Understanding the extent of genomic transcription and its functional relevance is a central goal in genomics research. However, detailed genome-wide investigations of transcriptome complexity in major mammalian organs have been scarce. Here, using extensive RNA-seq data, we show that transcription of the genome is substantially more widespread in the testis than in other organs across representative mammals. Furthermore, we reveal that meiotic spermatocytes and especially postmeiotic round spermatids have remarkably diverse transcriptomes, which explains the high transcriptome complexity of the testis as a whole. The widespread transcriptional activity in spermatocytes and spermatids encompasses protein-coding and long noncoding RNA genes but also poorly conserves intergenic sequences, suggesting that it may not be of immediate functional relevance. Rather, our analyses of genome-wide epigenetic data suggest that this prevalent transcription, which most likely promoted the birth of new genes during evolution, is facilitated by an overall permissive chromatin in these germ cells that results from extensive chromatin remodeling.